Rancang Bangun Sistem informasi Rekognisi Pembelajaran Lampau Menggunakan Metode Waterfall - Ariana Azimah; Heni Jusuf (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2023)
Starting from the 2023/2024 academic year, the National University (UNAS) accepts students from the Recognition of Past Learning (RPL) pathway. The purpose of implementing the RPL program at UNAS is to provide the widest possible opportunity for every individual who has received formal, non-formal or informal education through lifelong learning facilities, as well as providing equal opportunities for certain qualifications to a higher level, which in turn obtains proof of results. study in the form of a diploma. An information system is needed to manage the administration of RPL implementation from registration to obtaining credit (SKS) that are recognized to be able to continue education. The design method uses Waterfall because it is suitable for generic systems, namely the system can identify all its needs, starting from the beginning of building a system according to the chosen research topic until the product is tested. The test results show that the developed RPL information system application is running well in accordance with the system design.Keywords: Information system application; Recognition of past learning; Waterfalls AbstrakMulai tahun akademik 2023/2024 Universitas Nasional (UNAS) menerima mahasiswa jalur Rekognisi Pembelajaran Lampau (RPL). Tujuan dari penyelenggaan program RPL di UNAS adalah memberikan kesempatan seluas-luasnya bagi setiap individu yang telah menempu pendidikan formal, nonformal atau informal melalui fasilitas pembelajaran sepanjang hayat, serta memberikan kesempatan penyetaraan terhadap kualifikasi tertentu ke jenjang yang lebih tinggi, yang pada akhirnya memperoleh bukti hasil belajar berupa Ijazah. Diperlukan sistem informasi untuk mengelola administrasi pelaksanaan RPL mulai pendaftaran hingga perolehan kredit (SKS) yang diakui untuk dapat meneruskan pendidikan. Metode perancangan menggunakan Waterfall karena sesuai untuk sistem yang bersifat generik, yaitu sistem dapat mengidentifikasi semua kebutuhannya mulai dari awal membangun sebuah sistem sesuai dengan topik penelitian yang dipilih sampai dengan produk tersebut diuji. Hasil pengujian menunjukkan aplikasi sistem informasi RPL yang dikembangkan berjalan baik sesuai dengan rancangan sistem.